ChemInform Abstract: Synthesis of Monocyclic Nine‐Membered Compounds by the [4 + 3 + 2] Cycloaddition — Bond Cleavage Strategy. Issue 41 (19th September 2013) - Yamasaki, Ryu; Kato, Korehito; Hanitani, Daichi; Mutoh, Yuichiro; Saito, Shinichi
Abstract The Ni‐catalyzed cycloaddition of substrates (I) and (VII) provides bicyclic systems which consist of oxazine and nine‐membered ring moieties.